Expert clinical management of autoimmune hepatitis in the real world. Issue 5 (22nd December 2016) - Liberal, R.; de Boer, Y. S.; Andrade, R. J.; Bouma, G.; Dalekos, G. N.; Floreani, A.; Gleeson, D.; Hirschfield, G. M.; Invernizzi, P.; Lenzi, M.; Lohse, A. W.; Macedo, G.; et al.
Summary: Background: High‐quality data on the management of autoimmune hepatitis (AIH) are scarce. Despite published guidelines, management of AIH is still expert based rather than evidence based. Aim: To survey expert hepatologists, asking each to describe their practices in the management of patients with AIH. Methods: A survey questionnaire was distributed to members of the International AIH Group. The questionnaire consisted of four clinical scenarios on different presentations of AIH. Results: Sixty surveys were sent, out of which 37 were returned. None reported budesonide as a first line induction agent for the acute presentation of AIH. Five (14%) participants reported using thiopurine S‐methyltransferase measurements before commencement of thiopurine maintenance therapy. Thirteen (35%) routinely perform liver biopsy at 2 years of biochemical remission. If histological inflammatory activity is absent, four (11%) participants reduced azathioprine, whereas 10 (27%) attempted withdrawal altogether. Regarding the management of difficult‐to‐treat patients, mycophenolate mofetil is the most widely used second‐line agent ( n = ~450 in 28 centres), whereas tacrolimus ( n = ~115 in 21 centres) and ciclosporin ( n = ~112 in 18 centres) are less often reported. One centre reported considerable experience with infliximab, while rescue therapy with rituximab has been tried in seven centres. Conclusions: There is a wide variation in the management of patients with autoimmune hepatitis even among the most expert in the field. Although good quality evidence is lacking, there is considerable experience with second‐line therapies. Future prospective studies should address these issues, so that we move from an expert‐ to an evidence‐ and personalised‐based care in autoimmune hepatitis. Abstract : Linked Content This article is linked to Shen et al and de Boer et al papers. To view these articles visithttps://doi.org/10.1111/apt.14630 andhttps://doi.org/10.1111/apt.14651 .